Silver-based energy-saving heat-preservation film and heat-insulation energy-saving window film comprising same

By using silver nanowires to construct AgNWs/PEDOT/PSS or AgNWs/MXene coatings on glass doors, windows and curtain walls, a continuous grid structure is formed, which solves the problem of difficult balance between infrared emissivity and light transmittance in the prior art, and achieves efficient thermal isolation and energy-saving effects.

CN119798750APending Publication Date: 2025-04-11CHANGZHOU SANYOU DISSAN PROTECTIVE MATERIAL MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411742983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has limitations in improving the thermal insulation and insulation performance of glass doors, windows and curtain walls, especially when it is difficult to achieve a balance between reducing infrared emissivity and maintaining high light transmittance, and the preparation cost is high and the process is complicated.

Method used

The membrane material is constructed using silver nanowires (AgNWs), and a continuous grid structure is formed through AgNWs/PEDOT/PSS or AgNWs/MXene coating, which reduces the working area of ​​the light incident process and the silver film, reduces the plasma resonance absorption in the near infrared region, and controls the mesh size to be smaller than the far infrared wavelength, achieving a high reflection effect on the far infrared segment.

Benefits of technology

It achieves significant infrared reflectivity and good thermal isolation capabilities, reduces infrared emissivity, improves the energy-saving and thermal insulation performance of window films, ensures the balance of light transmittance and infrared reflectivity, and is suitable for use in areas such as building window films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798750A_ABST
    Figure CN119798750A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat insulation films, in particular to a silver-based energy-saving heat preservation film and a heat insulation energy-saving window film comprising the silver-based energy-saving heat preservation film, and the specific technical scheme is as follows: the silver-based energy-saving heat preservation film comprises a base material layer and a silver-based coating; the silver-based coating is an AgNWs / PEDOT / PSS (poly (3, 4-ethylenedioxythiophene) / poly (styrenesulfonate)) coating or an AgNWs / MXene coating; the average diameter of AgNWs in the silver-based coating ranges from 10 nm to 100 nm, and the average length of the AgNWs in the silver-based coating ranges from 10 micrometers to 30 micrometers. According to the silver-based energy-saving heat-preservation film and the heat-insulation energy-saving window film comprising the same, the film material is constructed by utilizing the silver nanowires, a continuous grid structure can be formed, on one hand, the action area of a light incidence process and a silver film is reduced, plasma resonance absorption in a near-infrared region is reduced, and on the other hand, by controlling the mesh size to be smaller than the far-infrared wavelength, the heat-insulation energy-saving window film can be formed. And the high reflection effect on the far infrared section is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat insulation films, and in particular to a silver-based energy-saving thermal insulation film and a heat insulation and energy-saving window film containing the same. Background Art

[0002] Glass doors, windows and curtain walls are the most important parts for indoor and outdoor energy exchange. Improving the thermal insulation and heat preservation performance of glass doors, windows and curtain walls plays an important role in energy conservation and carbon reduction.

[0003] In extremely cold regions or during extremely cold seasons, buildings consume a lot of heating energy to increase the indoor temperature, and most of the indoor heat is dissipated through windows with low thermal performance in the enclosure structure. Developing energy-saving windows with better performance can improve indoor energy efficiency and alleviate problems such as energy shortages and environmental pollution. The mid-infrared emissivity of ordinary window glass is 0.84, and its surface emissivity can be reduced through low-emissivity temperature control materials, thereby inhibiting the radiant heat exchange between the window and the environment.

[0004] One type of low-emissivity temperature control material is ultra-thin metal, such as silver film. Although metal film can significantly reduce the emissivity of the glass surface, its visible light transmittance is low, it is easily oxidized in the air, and its adhesion to the glass substrate is poor. The visible light transmittance, stability and durability of the metal film can be significantly improved through the optimized design of the multi-layer film system, but the complex processing technology also increases the preparation cost, limiting its practical application.

[0005] Another temperature control material with low emissivity is transparent conductive oxide (TCO), such as indium tin oxide (ITO). Compared with ultra-thin metals, TCO has higher visible light transmittance and better stability, but its mid-infrared emissivity is also relatively higher. Summary of the invention

[0006] The purpose of the present invention is to provide a silver-based energy-saving thermal insulation film and a heat-insulating energy-saving window film containing the same. The film material is constructed by using silver nanowires to form a continuous grid structure. On the one hand, the light incident process and the action area of ​​the silver film are reduced, and the plasma resonance absorption in the near-infrared region is reduced. At the same time, by controlling the mesh size to be smaller than the far-infrared wavelength, a high reflection effect in the far-infrared segment is achieved.

[0007] The above technical objectives of the present invention are achieved through the following technical solutions:

[0008] The present invention provides a silver-based energy-saving thermal insulation film, comprising a substrate layer and a silver-based coating; the silver-based coating is an AgNWs / PEDOT / PSS coating or an AgNWs / MXene coating; the average diameter of the AgNWs in the silver-based coating is 10 to 100 nm, and the average length is 10 to 30 μm.

[0009] Furthermore, the coating solution of the AgNWs / PEDOT / PSS coating includes AgNWs, PEDOT, PSS and a solvent, wherein the mass ratio of AgNWs, PEDOT and PSS is (0.4-2):(2-6):(2-6).

[0010] Furthermore, in the coating solution of the AgNWs / PEDOT / PSS coating, the concentration of AgNWs is calculated by the following formula:

[0011]

[0012] Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL;

[0013] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ;

[0014] D is the average diameter of AgNWs, in μm;

[0015] t is the coating thickness in μm;

[0016] L is the average length of AgNWs, in μm;

[0017] π is a constant, and its value is 3.1416.

[0018] Furthermore, the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating satisfies the following calculation model:

[0019] The value of N And the value of N

[0020] Where N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in units of pieces / mm 2 ;

[0021] L is the average length of AgNWs, in μm;

[0022] D is the average diameter of AgNWs, in μm;

[0023] A is the unit area, and its value is 1mm 2 ;

[0024] k is the proportional constant. When the coating is a single layer, the value is 5×10 -3 .

[0025] Furthermore, the coating liquid of the AgNWs / PEDOT / PSS coating is coated by micro-dimple coating, slit coating or wire rod coating.

[0026] Furthermore, the AgNWs / MXene coating comprises an AgNWs layer and a MXene layer;

[0027] The coating solution of the AgNWs layer includes AgNWs and a solvent, and the concentration of AgNWs in the coating solution of the AgNWs layer is calculated according to the following formula:

[0028]

[0029] Among them, C 1 is the concentration of AgNWs in the coating solution of the AgNWs layer, in mg / mL;

[0030] N is the mesh density of AgNWs in the AgNWs / MXene coating, in pieces / mm 2 ;

[0031] D is the average diameter of AgNWs, in μm;

[0032] t is the coating thickness in μm;

[0033] L is the average length of AgNWs, in μm;

[0034] π is a constant, with a value of 3.1416;

[0035] p is the adjustment factor.

[0036] Furthermore, in the AgNWs / MXene coating, when the coating method of the AgNWs coating liquid is spin coating, the value of p is 0.4 to 0.6.

[0037] The present invention also provides a heat-insulating and energy-saving window film comprising a silver-based energy-saving and thermal-insulating film, which has the same technical effect.

[0038] The heat-insulating and energy-saving window film comprising a silver-based energy-saving and heat-insulating film provided by the present invention comprises the following structures in sequence: a PET release protective film, a pressure-sensitive adhesive layer and a silver-based energy-saving and heat-insulating film.

[0039] Furthermore, when the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / PEDOT / PSS coating, the structure of the thermal insulation and energy-saving window film includes, in order: a PET release protective film, a pressure-sensitive adhesive layer, a nano-ceramic thermal insulation film, a composite adhesive layer, a silver-based energy-saving thermal insulation film and a hardened anti-oxidation coating.

[0040] Furthermore, when the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / MXene coating, the structure of the thermal insulation and energy-saving window film sequentially includes: a PET release protective film, an optical pressure-sensitive adhesive layer and a silver-based energy-saving thermal insulation film.

[0041] In summary, the present invention has the following beneficial effects:

[0042] OK, if we remove the descriptions about conductivity and electronic product films, the beneficial effects of silver-based energy-saving and thermal insulation films can be focused on energy saving and thermal insulation, with an emphasis on its application in areas such as building window films. The following are the modified beneficial effects:

[0043] (1) Silver-based coatings (AgNWs / PEDOT / PSS or AgNWs / MXene) have significant infrared reflectivity and good thermal insulation capabilities. They effectively reflect low, medium and far infrared radiation, reduce heat transfer, and improve the energy-saving and thermal insulation performance of window films. AgNWs / PEDOT / PSS coatings or AgNWs / MXene coatings reduce infrared emissivity, reduce the amount of solar radiation entering the room in summer, and effectively block indoor heat loss in winter, helping to achieve year-round energy-saving effects.

[0044] (2) By rationally designing the grid density and silver nanowire concentration, it is possible to ensure that the coating can maintain a high visible light transmittance while significantly improving the infrared reflectivity and achieving thermal isolation; the silver nanowires and MXene materials in the coating help maintain indoor light while isolating heat through their good infrared reflectivity and light transmittance. This balance enables the film to provide a comfortable indoor environment and effectively save energy.

[0045] (3) PEDOT MXene in both AgNWs / PEDOT / PSS coating and AgNWs / MXene coating has good chemical stability and mechanical strength, which makes the coating less likely to degrade during long-term use, ensuring the long-term reliability of the window film. Especially in the AgNWs / MXene coating, the layered structure of MXene material improves the stability of silver nanowires and enhances the oxidation resistance and high temperature resistance of the coating, making it suitable for application in high temperature and humidity environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a schematic structural diagram of the silver-based energy-saving and heat-insulating film according to Example 1 of the present invention;

[0047] Figure 2 This is a schematic diagram of the structure of the silver-based energy-saving and heat-insulating film according to Example 2 of the present invention;

[0048] Figure 3 This is a schematic structural diagram of a heat-insulating and energy-saving window film according to Embodiment 3 of the present invention;

[0049] Figure 4 This is a schematic structural diagram of the heat-insulating energy-saving window film according to Example 4 of the present invention.

[0050] Reference numerals

[0051] PET release protective film 1, pressure-sensitive adhesive layer 2, nano-ceramic thermal insulation film 3, composite adhesive layer 4, silver-based energy-saving thermal insulation film 5, substrate layer 51, AgNWs / PEDOT / PSS coating 52, AgNWs layer 53, MXene layer 54, hardened anti-oxidation coating 6, optical pressure-sensitive adhesive layer 7. DETAILED DESCRIPTION

[0052] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a silver-based energy-saving thermal insulation film and a heat-insulating energy-saving window film containing the same are proposed according to the present invention, and their specific implementation methods, characteristics and effects are described in detail as follows.

[0053] Existing vacuum glass, central control glass, etc., use the gas with low thermal conductivity in the interlayer to slow down the internal and external heat transfer, thereby playing the role of heat preservation and energy saving. However, in actual use, there are problems such as high cost, heavy weight, difficult installation, high replacement cost after damage, and inability to be used for the renovation of most existing buildings; Low-e glass is divided into online and offline Low-e glass. Among them, online Low-e glass generally has poor film thickness accuracy and cannot be made into a multi-layer film system; offline Low-e glass requires multi-layer coating to achieve good light transmittance and low emissivity. Common commercial single silver Low-e glass requires at least 5 layers of coating, double silver Low-e glass requires at least 9 layers of coating, and triple silver Low-e glass requires at least 13 layers of coating. The cost is high and the processing technology is complicated. It also cannot be used for the renovation of a large number of existing buildings; magnetron sputtering Low-e film, similar to Low-e glass, requires multi-layer coating to achieve good light transmittance and low emissivity. The process is still relatively complicated, the processing equipment is expensive, and the cost is relatively high.

[0054] In order to solve the above problems, the present specific embodiment provides a silver-based energy-saving and thermal insulation film, including a substrate layer and a silver-based coating; the silver-based coating is an AgNWs / PEDOT / PSS coating or an AgNWs / MXene coating; the average diameter of the AgNWs in the silver-based coating is 20 to 100 nm, and the average length is 10 to 30 μm.

[0055] It is understandable that silver is a metal material with extremely high reflectivity, especially in the far infrared (8-15μm) region. When AgNWs form a conductive network in the film, it can effectively reflect low, medium and far infrared radiation and reduce heat transfer. By optimizing the grid density and nanowire distribution, it can ensure a low emissivity without significantly affecting the transmittance. At the same time, the surface silver nanowires can excite surface plasmon resonance (LSPR) in the infrared band, effectively absorbing and reflecting infrared radiation, especially in the low infrared emissivity region. This effect helps to reduce the thermal radiation of the window film and improve the energy-saving performance.

[0056] In the AgNWs / MXene coating, MXene materials show high reflectivity in the infrared band, especially in the low-frequency infrared and mid-infrared bands (2-15μm). Therefore, the introduction of MXene can improve the reflectivity of the coating in the infrared band, thereby reducing the infrared emissivity of the coating. Through appropriate design and optimization, the combination of AgNWs and MXene can achieve more efficient infrared reflection and thermal isolation effects.

[0057] In the AgNWs / PEDOT / PSS coating, the polymer chain structure of PSS can enhance the mechanical strength and flexibility of the coating, making the coating have certain tensile and crack resistance. The addition of PEDOT not only provides conductivity, but also helps to adjust the resistance of the film, thereby affecting the infrared reflection performance, so that the coating maintains a higher infrared reflectivity while ensuring a lower resistance.

[0058] Exemplarily, the coating solution of the AgNWs / PEDOT / PSS coating includes AgNWs, PEDOT, PSS and a solvent, wherein the mass ratio of AgNWs, PEDOT and PSS is (0.4-2):(2-6):(2-6).

[0059] Exemplarily, in the coating solution of the AgNWs / PEDOT / PSS coating, the concentration of AgNWs is calculated by the following formula:

[0060]

[0061] Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL;

[0062] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ;

[0063] D is the average diameter of AgNWs, in μm;

[0064] t is the coating thickness in μm;

[0065] L is the average length of AgNWs, in μm;

[0066] ρ Ag 10.49 g / cm 3 ;

[0067] π is a constant, and its value is 3.1416.

[0068] It can be understood that the grid density N directly affects the distribution density and connection mode of the silver nanowires. A higher grid density increases the contact points between the silver nanowires, forming a tighter conductive network. The conductive performance is proportional to the grid density, because the number and quality of the conductive paths are closely related to the grid density. By adjusting the concentration of the coating solution, the concentration of the silver nanowires can be controlled, thereby controlling the grid density.

[0069] For example, the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating satisfies the following calculation model:

[0070] The value of N And the value of N

[0071] Where N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ;

[0072] L is the average length of AgNWs, in μm;

[0073] D is the average diameter of AgNWs, in μm;

[0074] A is the unit area, and its value is 1mm 2 ;

[0075] k is the proportional constant. When the coating is a single layer, the value is 5×10 -3 .

[0076] Preferably, the value of N is a middle value within the value range of the above calculation model.

[0077] It should be pointed out that when the coating is multi-layer, the value of k is 2×10 -3 .

[0078] It is understandable that too high a mesh density will increase the shading rate and reduce light transmittance, while too low a mesh density will result in too large a mesh gap, making it impossible to form a continuous conductive network, thus affecting infrared reflection. Infrared emissivity is closely related to the continuity of the mesh conductive network. Low mesh density: too large a gap will cause some infrared radiation to pass through or be absorbed, resulting in high emissivity; high mesh density: a continuous conductive network will be formed, effectively reflecting low, medium and far infrared radiation, thus reducing emissivity.

[0079] In this specific embodiment, the transmittance determines the transparency of the coating, which directly affects the degree of visible light transmission; while the infrared reflectivity determines the thermal isolation ability of the coating, affecting the ability to reflect infrared radiation. In many applications (such as window films), a balance needs to be struck between the two: increasing the transmittance to ensure sufficient indoor light, while increasing the infrared reflectivity to reduce heat conduction. By considering the target values ​​of both transmittance and infrared reflectivity, the optimal grid density can be found during the design process to ensure that the coating neither blocks light excessively nor effectively isolates heat, thereby achieving energy saving effects.

[0080] The grid density affects the conductive properties and optical properties (light transmittance and infrared reflectivity) of the coating. Too high a grid density will result in excessive shading and reduced light transmittance; too low a grid density will result in unstable conductive properties and may not achieve the required infrared reflectivity.

[0081] By calculating the mesh density with light transmittance and infrared reflectance as targets, it is possible to ensure that the coating optimizes both light transmittance and infrared performance while providing the required conductivity. This balanced design improves the overall performance of the coating, especially for applications requiring transparent conductive films and energy-saving windows.

[0082] In energy-saving applications (such as energy-saving window films), reducing infrared emissivity (i.e. increasing infrared reflectivity) can effectively prevent solar radiation heat from entering the room while ensuring visible light transmission, thereby reducing air-conditioning load and achieving energy saving.

[0083] By considering the target values ​​of light transmittance and infrared reflectance together, it is possible to ensure that the window film can maintain high light transmittance while effectively reflecting solar radiation, thereby allowing the building or vehicle to reduce energy consumption while maintaining indoor comfort.

[0084] Exemplarily, the coating liquid for coating the AgNWs / PEDOT / PSS coating layer is coated by micro-dimple coating, slit coating or wire bar coating.

[0085] Exemplarily, an AgNWs / MXene coating comprises an AgNWs layer and a MXene layer;

[0086] The coating solution of the AgNWs layer includes AgNWs and a solvent, and the concentration of AgNWs in the coating solution of the AgNWs layer is calculated according to the following formula:

[0087]

[0088] Among them, C 1 is the concentration of AgNWs in the coating solution of the AgNWs layer, in mg / mL;

[0089] N is the mesh density of AgNWs in the AgNWs / MXene coating, in pieces / mm 2 ;

[0090] D is the average diameter of AgNWs, in μm;

[0091] t is the coating thickness in μm;

[0092] L is the average length of AgNWs, in μm;

[0093] π is a constant, with a value of 3.1416;

[0094] p is the adjustment factor.

[0095] It can be understood that the calculation method of the grid density in the above formula is as mentioned above.

[0096] For example, in the AgNWs / MXene coating, when the coating method of the AgNWs coating liquid is spin coating, the value of p is 0.4 to 0.6.

[0097] It is understandable that when spin coating is selected, since the coating direction is complex and not a single uniform direction, the grid density of AgNWs will be higher. Therefore, the concentration of AgNWs is adjusted by using the adjustment coefficient P to avoid excessive grid density and affect the performance of the film.

[0098] This specific embodiment also provides a heat-insulating and energy-saving window film of a silver-based energy-saving and thermal-insulating film, characterized in that it includes the following structures in sequence: a PET release protective film, a pressure-sensitive adhesive layer and a silver-based energy-saving and thermal-insulating film.

[0099] Exemplarily, when the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / PEDOT / PSS coating, the structure of the thermal insulation and energy-saving window film includes, in order: a PET release protective film, a pressure-sensitive adhesive layer, a nano-ceramic thermal insulation film, a composite adhesive layer, a silver-based energy-saving thermal insulation film and a hardened anti-oxidation coating.

[0100] It is understandable that when the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / PEDOT / PSS coating, a hardened anti-oxidation layer needs to be applied.

[0101] Exemplarily, when the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / MXene coating, the structure of the heat-insulating energy-saving window film includes, in order: a PET release protective film, an optical pressure-sensitive adhesive layer, and a silver-based energy-saving thermal insulation film.

[0102] The present invention is further described below in conjunction with specific examples. It should be noted that the average diameter of the AgNWs used in the following specific examples is 50 nm and the average length is 20 μm.

[0103] Example 1

[0104] This embodiment 1 provides a silver-based energy-saving thermal insulation film, such as Figure 1 As shown, the sequence is substrate layer 51 and AgNWs / PEDOT / PSS coating layer 52 .

[0105] The substrate layer 51 is a PET film, and the AgNWs / PEDOT / PSS coating layer 52 is prepared from AgNWs, PEDOT (poly 3,4-ethylenedioxythiophene), PSS (polystyrene sulfonate) and solvent anhydrous ethanol.

[0106] The preparation method of the silver-based energy-saving thermal insulation film provided in this embodiment 1 is as follows:

[0107] S1. Adding AgNWs, PEDOT and PSS into anhydrous ethanol, and magnetically stirring for 1 h to mix them evenly, to form a coating solution of AgNWs / PEDOT / PSS coating with stable performance;

[0108] S2. The coating liquid of the AgNWs / PEDOT / PSS coating is evenly coated on the surface of the PET film by wire rod coating, and then dried and solidified in an oven at 60° C. to obtain a silver-based energy-saving and thermal insulation film.

[0109] Among them, the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating is calculated by the following formula:

[0110]

[0111] Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL;

[0112] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 (number of silver nanowires per unit area);

[0113] D is the average diameter of AgNWs, 0.05 μm;

[0114] t is the coating thickness, 10 μm;

[0115] L is the average length of AgNWs, 20 μm;

[0116] ρ Ag 10.49 g / cm 3 ;

[0117] π is a constant with a value of 3.1416.

[0118] The grid density of AgNWs in the AgNWs / PEDOT / PSS coating is determined by the following calculation model:

[0119] The value of N and the value of N

[0120] where N is the grid density of AgNWs in the AgNWs / PEDOT / PSS coating, with the unit of number / mm 2 ;

[0121] L is the average length of AgNWs, with the unit of μm;

[0122] D is the average diameter of AgNWs, with the unit of μm;

[0123] A is the unit area with a value of 1 mm 2 ;

[0124] T is the target light transmittance with a value of 85%;

[0125] k is a proportionality constant. When the coating is a single layer, its value is 5×10 -3 .

[0126] Then 12,500 number / mm 2 < N < 150,000 number / mm 2 , and the intermediate value is taken as N = 50,000 number / mm 2 ; Then substituting into the above formula, it can be known that in the coating solution of the AgNWs / PEDOT / PSS coating, the concentration of AgNWs is 0.49 mg / mL. According to the mass ratio of AgNWs, PEDOT, and PSS being 1:1.5:2.5, the concentration of PEDOT is 0.74 mg / mL, and 1.23 mg / mL.

[0127] Example 2

[0128] This Example 2 provides a silver-based energy-saving and heat-insulating film, as Figure 2 shown, with the sequence being a substrate layer 51, an AgNWs layer 53, and an MXene layer 54.

[0129] Among them, the substrate layer 1 is a PET film.

[0130] The preparation method of the silver-based energy-saving and heat-insulating film provided in this Example 2 is as follows:

[0131] A1. Clean the PET film with deionized water and absolute ethanol respectively, and dissolve AgNWs in absolute ethanol for dilution;

[0132] A2, spin-coating the diluted AgNWs solution onto the surface of the PET film, and then drying and curing it in an oven at 120°C to form a PET-AgNWs film;

[0133] A3. Spray MXene (concentration 1.5 mg / l) on the surface of AgNWs (Ti 3 C 2 T x ), and spraying was repeated 4 times to obtain a silver-based energy-saving thermal insulation film.

[0134] The concentration of AgNWs is calculated by the following formula:

[0135]

[0136] C 1 is the concentration of AgNWs, in mg / mL;

[0137] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 (number of silver nanowires per unit area);

[0138] D is the average diameter of AgNWs, 0.05 μm;

[0139] t is the coating thickness, 10 μm;

[0140] L is the average length of AgNWs, 20 μm;

[0141] ρ Ag 10.49 g / cm 3 ;

[0142] π is a constant, with a value of 3.1416;

[0143] The value of p is 0.5.

[0144] The mesh density of AgNWs is determined by the following calculation model:

[0145] The value of N And the value of N

[0146] Where N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in units of pieces / mm 2 ;

[0147] L is the average length of AgNWs, in μm;

[0148] D is the average diameter of AgNWs, in μm;

[0149] A is the unit area, with a value of 1 mm 2 ;

[0150] T is the target light transmittance, with a value of 85%;

[0151] k is the proportionality constant. When the coating is a single layer, its value is 5×10 -3 .

[0152] Then 12,500 pieces / mm 2 <N<150,000 pieces / mm 2 , and the intermediate value is taken as N = 50,000 pieces / mm 2 ; Then according to the above formula calculation, the concentration of AgNWs is 0.25 mg / mL.

[0153] Example 3

[0154] This Example 3 provides a heat-insulating and energy-saving window film, the structure of which is as Figure 3 shown, including in sequence: PET release protective film 1, pressure-sensitive adhesive layer 2, nano-ceramic heat-insulating film 3, composite adhesive layer 4, silver-based energy-saving and heat-preserving film 5, and hardening and antioxidant coating 6.

[0155] Among them, the silver-based energy-saving and heat-preserving film 5 is the silver-based energy-saving and heat-preserving film prepared in Example 1.

[0156] Then the preparation method of the heat-insulating and energy-saving window film is as follows:

[0157] P1. Coating a layer of acrylic resin hardening and antioxidant coating on the AgNWs / PEDOT / PSS coating surface of the silver-based energy-saving and heat-preserving film 5 with a wire bar. After coating, it is first dried in an oven and then cured by a UV curing machine;

[0158] P2. Coating a layer of composite adhesive layer on the other side of the base material layer of the silver-based energy-saving and heat-preserving film 5. After drying and curing in an oven, a nano-ceramic heat-insulating film is laminated;

[0159] P3. Coating a layer of polyacrylate pressure-sensitive adhesive layer on the other side of the nano-ceramic heat-insulating film. After the adhesive layer is dried and cured in an oven, a PET release protective film is laminated, thus forming a heat-preserving window film product with a low mid- and far-infrared emissivity.

[0160] After testing, the light transmittance of the prepared product at 550 nm is about 70%, and the emissivity at 7 - 14 μm is as low as 45%.

[0161] Example 4

[0162] This Example 4 provides a heat-insulating and energy-saving window film, the structure of which is as Figure 4 shown, including in sequence: PET release protective film 1, optical pressure-sensitive adhesive layer 7, and silver-based energy-saving and heat-preserving film 5.

[0163] The silver-based energy-saving and heat-insulating film 5 used in this embodiment 4 is the silver-based energy-saving and heat-insulating film prepared in embodiment 2.

[0164] The preparation method of the heat-insulating energy-saving window film is as follows: a layer of optical pressure-sensitive adhesive is coated on the non-coated surface of the silver-based energy-saving thermal insulation film 5, and then a PET release film is attached after drying and curing in an oven.

[0165] After testing, the prepared PET-AgNWs-MXene window film product can achieve a visible light transmittance of 70% in the range of 300-800nm, and an emissivity as low as 36.8% in the range of 7-14μm, which has good thermal insulation and energy-saving effects.

[0166] Comparative Example 1

[0167] This comparative example 1 is the same as the example 3, except that the silver-based energy-saving thermal insulation film used is a substrate layer and an AgNWs / PEDOT / PSS coating in that order.

[0168] The substrate layer is a PET film, and the AgNWs / PEDOT / PSS coating is prepared from AgNWs, PEDOT (poly 3,4-ethylenedioxythiophene), PSS (polystyrene sulfonate) and solvent anhydrous ethanol.

[0169] The preparation method of the silver-based energy-saving thermal insulation film provided in this comparative example 1 is as follows:

[0170] S1. Adding AgNWs, PEDOT and PSS into anhydrous ethanol, and magnetically stirring for 1 h to mix them evenly, to form a coating solution of AgNWs / PEDOT / PSS coating with stable performance;

[0171] S2. The coating liquid of the AgNWs / PEDOT / PSS coating is evenly coated on the surface of the PET film by wire rod coating, and then dried and solidified in an oven at 60° C. to obtain a silver-based energy-saving and thermal insulation film.

[0172] Among them, the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating is calculated by the following formula:

[0173]

[0174] Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL;

[0175] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 (number of silver nanowires per unit area);

[0176] D is the average diameter of AgNWs, 0.05 μm;

[0177] t is the coating thickness, 10 μm;

[0178] L is the average length of AgNWs, 20 μm;

[0179] ρ Ag 10.49 g / cm 3 ;

[0180] π is a constant, and its value is 3.1416.

[0181] The grid density of AgNWs in the AgNWs / PEDOT / PSS coating is 10000 / mm 2 .

[0182] Substituting into the above formula, it can be seen that in the coating solution of AgNWs / PEDOT / PSS coating, the concentration of AgNWs is 0.1 mg / mL. According to the mass ratio of AgNWs, PEDOT and PSS of 1:1.5:2.5, the concentration of PEDOT is 0.15 mg / mL and 0.25 mg / mL.

[0183] Comparative Example 2

[0184] This comparative example 2 is the same as the example 3, except that the silver-based energy-saving thermal insulation film used is a substrate layer and an AgNWs / PEDOT / PSS coating in that order.

[0185] The substrate layer is a PET film, and the AgNWs / PEDOT / PSS coating is prepared from AgNWs, PEDOT (poly 3,4-ethylenedioxythiophene), PSS (polystyrene sulfonate) and solvent anhydrous ethanol.

[0186] The preparation method of the silver-based energy-saving thermal insulation film provided in this comparative example 2 is as follows:

[0187] S1. Adding AgNWs, PEDOT and PSS into anhydrous ethanol, and magnetically stirring for 1 h to mix them evenly, to form a coating solution of AgNWs / PEDOT / PSS coating with stable performance;

[0188] S2. The coating liquid of the AgNWs / PEDOT / PSS coating is evenly coated on the surface of the PET film by wire rod coating, and then dried and solidified in an oven at 60° C. to obtain a silver-based energy-saving and thermal insulation film.

[0189] Among them, the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating is calculated by the following formula:

[0190]

[0191] Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL;

[0192] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 (number of silver nanowires per unit area);

[0193] D is the average diameter of AgNWs, 0.05 μm;

[0194] t is the coating thickness, 10 μm;

[0195] L is the average length of AgNWs, 20 μm;

[0196] ρ Ag 10.49 g / cm 3 ;

[0197] π is a constant, and its value is 3.1416.

[0198] The grid density of AgNWs in the AgNWs / PEDOT / PSS coating is 100,000 / mm 2 .

[0199] Substituting into the above formula, it can be seen that in the coating solution of AgNWs / PEDOT / PSS coating, the concentration of AgNWs is 0.98 mg / mL. According to the mass ratio of AgNWs, PEDOT and PSS of 1:1.5:2.5, the concentration of PEDOT is 1.47 mg / mL and 2.45 mg / mL.

[0200] Comparative Example 3

[0201] This comparative example 2 is the same as example 4, except that the silver-based energy-saving thermal insulation film used is a substrate layer, an AgNWs layer, and a MXene layer in that order.

[0202] The substrate layer 1 is a PET film.

[0203] The preparation method of the silver-based energy-saving thermal insulation film provided in this comparative example 3 is as follows:

[0204] A1. Use deionized water and anhydrous ethanol to clean the PET film, and dissolve the AgNWs in anhydrous ethanol;

[0205] A2, spin-coating the diluted AgNWs solution onto the surface of the PET film, and then drying and curing it in an oven at 120°C to form a PET-AgNWs film;

[0206] A3. Spray MXene (concentration 1.5 mg / l) on the surface of AgNWs (Ti 3 C 2 T x ), and spraying was repeated 4 times to obtain a silver-based energy-saving thermal insulation film.

[0207] The concentration of AgNWs is calculated by the following formula:

[0208]

[0209] C 1 is the concentration of AgNWs, in mg / mL;

[0210] N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 (number of silver nanowires per unit area);

[0211] D is the average diameter of AgNWs, 0.05 μm;

[0212] t is the coating thickness, 10 μm;

[0213] L is the average length of AgNWs, 20 μm;

[0214] ρ Ag 10.49 g / cm 3 ;

[0215] π is a constant, with a value of 3.1416;

[0216] The value of p is 1.

[0217] The mesh density of AgNWs is determined by the following calculation model:

[0218] The value of N And the value of N

[0219] Where N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ;

[0220] L is the average length of AgNWs, in μm;

[0221] D is the average diameter of AgNWs, in μm;

[0222] A is the unit area, and its value is 1mm 2 ;

[0223] T is the target transmittance, which is 85%;

[0224] k is a proportionality constant, which takes the value of 5×10 when the coating is a single layer. -3 .

[0225] Then 12,500 per mm 2 <N < 150,000 per mm 2 , and the intermediate value is taken as N = 50,000 per mm 2 ; Then according to the above formula calculation, the concentration of AgNWs is 0.49 mg / mL.

[0226] Performance Test

[0227] The visible light transmittance and emissivity at wavelengths of 7 - 14 μm of the window films prepared in Example 3, Example 4 and Comparative Example 1 - 3 were respectively tested, and the test results are shown in the following table.

[0228]

[0229]

[0230] According to the comparison of the test results of Example 3 with Comparative Example 1 and Comparative Example 2, when the grid density of AgNWs does not meet the calculation model provided by the present invention, the window film cannot simultaneously meet the requirements of light transmittance and infrared reflectance.

[0231] It should be noted that according to the comparison of the test results of Example 4 and Comparative Example 3, when spin coating is used, if the concentration of AgNWs is not adjusted by the p value, it will also cause an increase in the grid density of AgNWs, resulting in a significant decrease in the light transmittance of the window film.

[0232] The above are only the preferred embodiments of the present invention, and do not impose any form of limitation on the present invention. Although the present invention has been shown above with the preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments by using the above - disclosed technical content within the scope of the technical solution of the present invention. However, as long as it does not depart from the content of the technical solution of the present invention, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A silver-based energy-saving thermal insulation film, characterized in that: It comprises a substrate layer and a silver-based coating; the silver-based coating is an AgNWs / PEDOT / PSS coating or an AgNWs / MXene coating; the average diameter of the AgNWs in the silver-based coating is 10 to 100 nm, and the average length is 10 to 30 μm.

2. The silver-based energy-saving thermal insulation film according to claim 1, characterized in that: The coating liquid of the AgNWs / PEDOT / PSS coating comprises AgNWs, PEDOT, PSS and a solvent, wherein the mass ratio of AgNWs, PEDOT and PSS is (0.4-2):(2-6):(2-6).

3. The silver-based energy-saving thermal insulation film according to claim 2, characterized in that: In the coating solution of the AgNWs / PEDOT / PSS coating, the concentration of AgNWs is calculated by the following formula: Wherein, C is the concentration of AgNWs in the coating solution of AgNWs / PEDOT / PSS coating, in mg / mL; N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ; D is the average diameter of AgNWs, in μm; t is the coating thickness in μm; L is the average length of AgNWs, in μm; π is a constant with a value of 3.1416.

4. The silver-based energy-saving thermal insulation film according to claim 3, characterized in that: The mesh density of AgNWs in the AgNWs / PEDOT / PSS coating satisfies the following calculation model: The value of N> And the value of N < Where N is the mesh density of AgNWs in the AgNWs / PEDOT / PSS coating, in pieces / mm 2 ; L is the average length of AgNWs, in μm; D is the average diameter of AgNWs, in μm; A is the unit area, and its value is 1mm 2 ; T is the target transmittance, in %; k is the proportional constant. When the coating is a single layer, the value is 5×10 -3 .

5. A silver-based energy-saving thermal insulation film according to claim 3 or 4, characterized in that: The coating liquid of the AgNWs / PEDOT / PSS coating is coated by micro-dimple coating, slit coating or wire rod coating.

6. The silver-based energy-saving thermal insulation film according to claim 1, characterized in that: The AgNWs / MXene coating comprises an AgNWs layer and a MXene layer; The coating solution of the AgNWs layer includes AgNWs and a solvent, and the concentration of AgNWs in the coating solution of the AgNWs layer is calculated according to the following formula: Wherein, C1 is the concentration of AgNWs in the coating solution of the AgNWs layer, in mg / mL; N is the mesh density of AgNWs in the AgNWs / MXene coating, in pieces / mm 2 ; D is the average diameter of AgNWs, in μm; t is the coating thickness in μm; L is the average length of AgNWs, in μm; π is a constant, with a value of 3.1416; p is the adjustment factor.

7. The silver-based energy-saving thermal insulation film according to claim 6, characterized in that: In the AgNWs / MXene coating, when the coating method of the AgNWs coating liquid is spin coating, the p value is 0.4 to 0.

6.

8. A heat-insulating and energy-saving window film comprising the silver-based energy-saving and thermal-insulating film according to any one of claims 1 to 7, characterized in that: The sequence includes the following structures: a PET release protective film, a pressure-sensitive adhesive layer and a silver-based energy-saving thermal insulation film.

9. The heat-insulating and energy-saving window film according to claim 8, characterized in that: When the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / PEDOT / PSS coating, the structure of the thermal insulation and energy-saving window film includes, in order: a PET release protective film, a pressure-sensitive adhesive layer, a nano-ceramic thermal insulation film, a composite adhesive layer, a silver-based energy-saving thermal insulation film and a hardened anti-oxidation coating.

10. The heat-insulating and energy-saving window film according to claim 8, characterized in that: When the silver-based coating of the silver-based energy-saving thermal insulation film is an AgNWs / MXene coating, the structure of the heat-insulating energy-saving window film includes, in sequence: a PET release protective film, an optical pressure-sensitive adhesive layer, and a silver-based energy-saving thermal insulation film.